2011
DOI: 10.4103/0378-6323.77452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and bacteriological profile and outcome of sepsis in dermatology ward in tertiary care center in New Delhi

Abstract: Sepsis occurred in 40 (4.65%) inpatients in dermatology ward. The frequency of sepsis was highest in TEN (90%), followed by drug-induced maculopapular rash (20.0%), erythroderma (17.5%), and vesicobullous diseases (8.5%). MRSA, acinetobacter, pseudomonas, MSSA, and Klebsiella were important etiological agents involved in sepsis in dermatology in-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…This is similar to the other Indian studies by Asati et al ., Sharma et al ., and Malhotra et al . [7810] A total of 36.1% of the cases in the present study had duration of illness less than two weeks duration, which chiefly comprised the primary pyodermas and eczemas, while long duration of illness was seen in the vesiculobullous group. Many studies have shown that the duration of illness was found to correlate with the risk of MRSA infection, especially in cases of autoimmune vesiculobullous disorders.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This is similar to the other Indian studies by Asati et al ., Sharma et al ., and Malhotra et al . [7810] A total of 36.1% of the cases in the present study had duration of illness less than two weeks duration, which chiefly comprised the primary pyodermas and eczemas, while long duration of illness was seen in the vesiculobullous group. Many studies have shown that the duration of illness was found to correlate with the risk of MRSA infection, especially in cases of autoimmune vesiculobullous disorders.…”
Section: Discussionmentioning
confidence: 64%
“…[9] Male preponderance has been found in other Indian studies also. [710] However, in the study by Asati et al .,[8] there was a female preponderance.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations